2016
DOI: 10.1001/jamasurg.2015.4233
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Approach to the Treatment of Gastroesophageal Reflux Disease

Abstract: Gastroesophageal reflux disease is a highly prevalent disease. Once the diagnosis has been established, the best results are obtained by a multidisciplinary team with the goal of individualizing treatment for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
79
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 69 publications
0
79
1
13
Order By: Relevance
“…11 A study by Shaheen et al, who analyzed the healthcare costs for gastrointestinal and liver diseases, reported that in 2004 the sales of PPIs in the United States reached 10 billion dollars. 12 A proper work-up for patients with GERD-related symptoms could dramatically reduce this expense.…”
Section: Discussionmentioning
confidence: 99%
“…11 A study by Shaheen et al, who analyzed the healthcare costs for gastrointestinal and liver diseases, reported that in 2004 the sales of PPIs in the United States reached 10 billion dollars. 12 A proper work-up for patients with GERD-related symptoms could dramatically reduce this expense.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, up to 40% of patients fail to respond to PPIs, and there is an increasing concern that long‐term PPI maintenance may cause side effects such as reduced bone mineral density bone fracture and increasing the risk of myocardial infarction (MI), which has attracted more and more attention .Theoretically, prokinetic agents can improve the ability of esophageal acid clearance by enhancing esophageal peristalsis and augmenting the tension of LES, fundamentally preventing the occurrence of GERD; however, effective target drugs have not been developed. Additionally, successful antireflux surgery, such as Nissen fundoplication, can significantly reduce the chance of recurrence, but surgical complications and mortality are still a disturbing question concerning some surgeons’ experience and technique level .…”
Section: Introductionmentioning
confidence: 99%
“…8,23 Multiple studies have also concluded that a combination of hormonal changes and physical alterations increases the vulnerability of pregnant women to GORD especially in the third trimester. [24][25][26] The management of GORD includes both nonpharmacological and pharmacological approaches. Nonpharmacological treatment options include lifestyle modifications including changes in diet, sleeping posture, and weight reduction.…”
Section: Introductionmentioning
confidence: 99%